ANALISIS DESTINASI BUMDES BINOR TOUR CAFÉ DAN RESTO PANTAI BOHAY DENGAN RESERVASI PENUH - Eka Pradani, Riski Febri; Masyhur, Ahmad; Zainal Abidin, Moh Ali; Hidayat, Moh Noer; Iman, M kamilul (LP2M Universitas Bina Bangsa, 2025)
Bohay Paiton Beach, located in Probolinggo Regency, East Java, has developed into one of the leading tourist destinations with its alluring natural charm and culinary diversity served in cafes and restaurants around the beach. The increasing number of visitors each year, especially on weekends and the holiday season, has led to some eateries around the beach experiencing a surge in visitors, which triggers the need for an efficient reservation system. This study aims to analyze the factors that affect the high demand for cafes and restaurants at Bohay Paiton Beach, as well as their impact on the tourist experience. The method used is a descriptive qualitative approach with direct observation, interviews with managers and visitors, and customer satisfaction surveys. The results of the study show that the main factors that attract tourists are the quality of food, natural scenery, and the comfortable atmosphere offered by cafes and restaurants around the beach. The reservation system has proven to have a positive impact on the culinary experience of visitors, but managers still face challenges in managing the number of visitors, especially those who come without reservations. This study also found that the existence of cafes and restaurants on Bohay Paiton Beach has a significant impact on the local economy and the tourism sector in Probolinggo. Therefore, better management, especially in the implementation of the reservation system and visitor management, is needed to improve the tourist experience and maximize the tourism potential in this area.